ETHNOGRAPHY RESEARCH IN EDUCATIONAL: A LITERATURE REVIEW - Andi Hamzah Fansury; Rampeng Rampeng (Teaching English as a Foreign Language Overseas Journal, 2023)
Ethnography is a type of qualitative research that gathers observations, interviews, and documentary data to produce detailed and comprehensive accounts of different social phenomena. Ethnographic study helps in developing the theoretical base for problems in education of a particular group. Ethnographic research does not often start with a strong theoretical base, not it is much concerned with theory testing. There may be theory development, but formal theory enters research only after its relevance has been established. In ethnographic research, theory emerges from the data as grounded theory- not as preconceived theory. Ethnographic study helps in the development of a theory as it does not simply tabulate that a certain behavior has occurred, but it attempts to understand what the behavior means the persons under study.